The importance of Böhler’s Angle in Calcaneus Geometry: A Finite Element Model Study - Gültekin, Alper; Acar, Erdinç; Uğur, Levent; Yıldız, Aytaç; Serarslan, Ulaş (Turkish Joint Diseases Foundation, 2021)
Objectives: Calcaneal fractures are the most common tarsal fractures following a foot-ankle trauma. The Böhler’s angle is an important measurable angle before, during, and after surgery. In this study, we aimed to investigate correlation between Böhler’s angle, calcaneal strength, and subtalar joint stress using a finite element analysis (FEA). Patients and methods: Between January 2016 and December 2016, computed tomography (CT) scans were used with MIMICS® software for FEA. The ankle and foot of a 23-year-old male person with a height of 180 cm and weighing 80 kg was modeled as reference. Raw coronal CT images were obtained in Digital Imaging and Communications in Medicine format with the resolution of 512¥512 pixels and 0.3-mm slice intervals in 135 kV. The structures including tibia, fibula and 26 other bones (talus, calcaneus, cuboid, navicular, three cuneiforms, five metatarsals, and 14 components of phalanges), cartilage and ligamentous tissues were modeled to form ankle joint. After determining Böhler’s angle as 35 degrees for the reference model, a fracture line was created on calcaneus. Calcaneus was remodeled with the Böhler’s angle of 45, 40, 30, 25, 20, 10, and 0 degrees respectively. All models were transferred to ANSYS software for FEA and the loads on the lower extremities with normal posture were applied on models. Results: Analysis of all models based in the reference model revealed that maximum tension values on calcaneus increased, while the Böhler’s angle decreased, indicating a statistically significant difference. The decreased Böhler’s angle indicated statistically significantly higher maximum tension values (p=0.04). Action force in subtalar joint was evaluated by comparing with the forces in reference model. The increased Böhler’s angle was found to be associated with statistically significantly decreased amount of load on subtalar joint. The decreased Böhler’s angle was related to the statistically significantly increased amount of load on subtalar joint. Conclusion: Our study results suggest that decreased Böhler’s angle increases the possibility of subtalar arthrosis, although overcorrection of the Böhler’s angle seems not to increase the risk of subtalar arthrosis.
Keywords: Biomechanics; Böhler; calcaneus; finite element analysis; fracture; subtalar arthrosis